Comparative effectiveness of amphotericin B, azoles and echinocandins in the treatment of candidemia and invasive candidiasis: A systematic review and network meta‐analysis. Issue 9 (9th May 2021) - Demir, Koray K.; Butler‐Laporte, Guillaume; Del Corpo, Olivier; Ekmekjian, Taline; Sheppard, Donald C.; Lee, Todd C.; Cheng, Matthew P.
Abstract: Background + Objectives: The echinocandins, amphotericin B preparations, voriconazole and fluconazole are approved for the treatment of invasive candidiasis, though it remains unclear which agent is most effective. In order to answer this question, we performed a systematic review and network meta‐analysis of the randomised controlled trials (RCTs) which evaluated these agents in comparison. Methods: Four electronic databases were searched from database inception to 8 October 2020. RCTs comparing triazoles, echinocandins or amphotericin B for the treatment of invasive candidiasis or candidemia were included. Random effect Bayesian network meta‐analysis methods were used to compare treatment outcomes. Results: Thirteen RCTs met inclusion criteria. Of the 3528 patients included from these trials, 1531 were randomised to receive an echinocandin, 944 to amphotericin B and 1053 to a triazole. For all forms of invasive candidiasis, echinocandins were associated with the highest rate of treatment success when compared to amphotericin B (OR 1.41, 95% CI 1.04–1.92) and the triazoles (OR 1.82, 95% CI 1.35–2.51). Rank probability analysis favoured echinocandins as the most effective choice 98% of the time. Overall survival did not significantly differ between groups. Conclusions: Among patients with invasive candidiasis, echinocandins had the best clinical outcomes and should remain the first‐line agents in the treatment of invasive candidiasis.